European gothic : a spirited exchange, 1760-1960 - Horner, Avril, 1947-; Manchester University Press (Manchester, UK : Manchester University Press, 2017)
The book charts the rich process of cross-fertilisation, especially regarding Anglo-French exchanges in the development of the Gothic novel and emphasises the importance of the impact of translation on the development of the Gothic novel. Each chapter offers a fresh way of thinking about Gothic lineages and histories. This work uses a variety of critical perspectives to reassess the work of authors such as Clara Reeve, Sophia Lee, Charlotte Smith, Ann Radcliffe, Matthew Lewis, Charles Maturin, Coleridge, Mary Shelley, Jan Potocki, Balzac, Dostoevesky, Gaston Leroux and Djuna Barnes.
The only collection to concentrate on the European Gothic - writing in English, French, German, Russian and Spanish. Charts the rich process of cross-fertilisation, especially regarding Anglo-French exchanges in the development of the Gothic novel. Emphasises the importance of the impact of translation on the development of the Gothic novel. Uses a variety of critical perspectives to reassess the work of authors such as Clara Reeve, Sophia Lee, Charlotte Smith, Ann Radcliffe, Matthew Lewis, Charles Maturin, Coleridge, Mary Shelley, Jan Potocki, Balzac, Dostoevesky, Gaston Leroux and Djuna Barnes. Offers a fresh way of thinking about Gothic lineages and histories.
Introduction -- Avril Horner 1. Translation in distress: Cultural misappropriation and the construction of the Gothic -- Terry Hale 2. European disruptions of the idealized woman: Matthew Lewis's The Monk and the Marquis de Sade's Le Nouvelle Justine -- Angela Wright 3. Diderot and Maturin: Enlightenment, automata and the theatre of terror -- Victor Sage 4. Verging on the Gothic: Melmoth's journey to France -- Catherine Lanone 5. Europhobia: the Catholic other in Horace Walpole and Charles Maturin -- Robert Miles 6. European Gothic and nineteenth-century Russian literature -- Neil Cornwell 7. The robbers and the police: British romantic drama and the Gothic treacheries of Coleridge's Remorse -- Peter Mortensen 8. Translating Mary Shelley's Valperga into English: Historical romance, biography or Gothic fiction -- John Williams 9. 'Hallelujah to your dying screams of torture': Representations of ritual violencein English and Spanish Romanticism -- Joan Curbet 10. Potocki's Gothic arabesque: Embedded narrative and the treatment of boundaries in The Manuscript Found in Saragossa (1797-1815) -- Ahlam Alaki 11. The Gothic crosses the Channel: Abjection and revelation in Le Fantôme de l'Opéra -- Jerrold E. Hogle 12. 'A detour of filthiness': French fiction and Djuna Barnes's Nightwood -- Avril Horner.
Includes bibliographical references and index.
In English.
Print version record
JSTOR
Keywords: Gothic literature -- History and criticism; Gothic revival (Literature) -- Europe; European fiction -- History and criticism; European fiction -- 19th century -- History and criticism; Roman européen -- 19e siècle -- Histoire et critique; Roman européen -- Histoire et critique; Littérature frénétique -- Europe; Littérature gothique -- Histoire et critique; 17.86 literary genres, theory of genre; Literature; Literature -- History & Criticism; LITERARY CRITICISM -- General; LITERARY CRITICISM / General; Gothic revival (Literature); Gothic literature; European fiction; Europe; Gothic novel; Schauerroman; Aufsatzsammlung; Europa; Gothic Revival (letterkunde); Gothic novel; Griezelromans; Literature -- History & criticism; 1800-1899; Electronic books; Criticism, interpretation, etc